Analysis Of Solar Energy Utilization Of Hybrid Systems For Freezing Mango Fruit - Yudhy Kurniawan; M. Idrus Alhamid; Ardiyansyah Yatim (Universitas Respati Yogyakarta, 2023)
The use of vapour compression refrigeration systems is growing both on a domestic and commercial scale. The impact of electrical energy consumption in this sector is quite large compared to the need for electrical energy in other electronic equipment. Various efforts were made to be able to reduce the consumption of electrical energy for the cooling system. One of the efforts made by utilizing the natural potential of energy around is solar energy and wind energy as a source of electrical energy in the freezing unit of mango fruit. This fruit is one of the main commodities in West Java, especially in Indramayu district. The purpose of this study is to find out the needs of electricity consumption and how efficient the use of alternative energy is for freezing mango fruit. Inthe process freezing is carried out at temperatures below the freezing point of the food. Good freezing usually ranges from -12 oC to -24 oC. With this temperature, food can last up to 3 to 12 months. In this study, the method was carried out for freezing mangoes by utilizing solar energy which was assembled hybrid with wind energy in the vapour compression refrigeration system for the freezing. The design method is carried out by taking into account the cooling load on the freezer to find out the cooling capacity is 1/2 PK. The test results can be analyzed comparing the performance of the utilization of the hybrid energy system with the design and use of PLN electricity, the length of time to reach the freezing temperature of a unit.